Developmental Exposure to Very Low Levels of Ethynilestradiol Affects Anxiety in a Novelty Place Preference Test of Juvenile Rats - Zaccaroni, Marco; Seta, Daniele Della; Farabollini, Francesca; Fusani, Leonida; Dessì-Fulgheri, Francesco (Neurotoxicity research, 2016)
Ethinylestradiol (EE 2 ), a synthetic mimic of 17β-estradiol, is widespread in the environment because of its use as a contraceptive. In mammals, recent research highlighted behavioral, physiological, and morphological effects of exposition to EE 2 (this xenoestrogen). We studied if developmental exposure to environmental-like, low doses of EE 2 affects measures of anxiety in Sprague–Dawley rats. We treated male and female rats with two doses of EE 2 (4 and 400 ng/kg/day) either from GD 5 through PND 32 or from PND 1 through 21. Effects on anxiety were tested by novel place preference tests. In males and females treated from GD 5 through PND 32, a significant reduction of the time passed in the novel environment was observed. The decrease of the time spent in the novel compartment and the increase in the number of transitions between familiar and novel compartments indicate increased levels of anxiety in the EE 2 -treated subjects. These studies suggest that exposure to very low doses of EE 2 during development can affect key behavioral traits that are modulated by anxiety.